Shifting to Online Learning in University in COVID-19 Pandemic (Comparative & International Education Series, 2022)
This chapter examines lecturers’ experiences of shifting from physical classrooms to online learning and their strategies for managing online learning after the outbreak of the COVID-19 pandemic in Nepal. This qualitative research employed semi-structured interviews and observation to collect data. We report that lecturers’ practice of online learning has changed their traditional beliefs about face-to-face teaching practices. Online workshops and webinars enabled them to identify and use information and communication technologies (ICTs) for online teaching in pandemic lockdowns. Despite their limited knowledge of ICT and e-pedagogies, they created online group forums and engaged students in collaborative learning activities. This resulted in students’ off-class communications and increased their learning autonomy in online classes. Lecturers managed to teach many students in a short period of online courses despite unreliable electricity and the Internet. Systematic development of online education can provide students equal opportunities for quality education.How to cite in APA:Adhikari, S. R., & Rana, K. (2022). Shifting to online learning in university in COVID-19 pandemic. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 141-154). STAR Scholars.